Los grupos “desarrollistas” y su incidencia en el espacio urbano de la ciudad de Córdoba, Argentina (1990- 2013) - Capdevielle, Julieta María (2014)
In the context of the economic recovery after the crisis of 2001, in the city of Córdoba it became relevant and centrality the actions of different “developers” groups that have a divergence power over space. From the relational approach in which we position we consider the socio-spatial dynamics and transformations of Córdoba city can not be understood without taking into account the interests, feelings and strategies deployed by these groups. Thus, throughout this essay we seek to analyze the continuities and transformations in this sector and its impact on urban space. We conclude, by considering these groups became one of the principal architects of the socio-territorial transformations, these resulted in a sharp intensification and commodification of urban land consolidating a model of inclusive and exclusive city to large segments of the population.